The Effect of Using Simple Aircraft Concrete Media on the Mastery of Concepts in Inquiry Science Learning in Elementary School Students - Erni Asmawati; Muhamad Taufik Bintang Kejora (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2020)
This study aims to determine the increase in mastery of concepts in inquiry learning science through simple concrete media. This research is expected to help teachers solve the problems of learning science at the elementary school level. The research approach used quantitative research with a quasi-experimental method and a nonequivalent control group design. The study involved 60 fifth grade students of SDN 1 Nagrikidul, Purwakarta district. In the control class, conventional learning assisted by audio-visual media is applied. And the experimental class applied science learning by inquiry using concrete media. The results showed that the gain normalization test for increasing the mastery of science concepts in the experimental class (N-gain 0.44) was greater than the control class's gain value (N-gain 0.23). Based on the test results, the difference between the two means is obtained count = 3.368 ttable = 2.045, with a sig. 0.002 α amounting to 0.05, then H0 is rejected, and Ha is accepted. Therefore Inquiry science learning by utilizing concrete media can significantly improve the mastery of science concepts in elementary school students.